They can handle it, they are leaders: a look into organizational leaders’ mental health - Josephine Octavia; Kususanto Ditto Prihadi; Hong Chun Yeoh; Endah Kurniawati Purwaningtyas (Intelektual Pustaka Media Utama, 2022)
Few studies have examined the mental health of people in a leadership positions. Most of the time, mental health-related policies were created for the non-leaders to cope with the perceived pressure from their leaders. Nevertheless, the mental health of organizational leaders itself might be at stake due to the leadership ‘acts’ they have to perform. This current study aims to investigate the moderating effect of social support and self-compassion on the relationship between organizational leaders’ emotional labor and their psychological well-being. A hundred and twentyone mid-level working executives in leadership positions provided data on their emotional labor, social support, self-compassion, and psychological well-being. It was predicted that social support and self-compassion will both moderate the relationship between organizational leaders’ emotional labor and their psychological well-being. The results indicated that surface acting is correlated with psychological wellbeing while deep acting is not. Social support and self-compassion do not moderate the relationship between emotional labor and psychological wellbeing. However, age is significantly correlated with psychological wellbeing, social support, and self-compassion, indicating its importance in leaders. Implications and limitations are discussed